2020
DOI: 10.3390/su12083192
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral Analysis of Landscape Interiors (SALI) as One of the Tools for Monitoring Changes in Green Infrastructure Systems

Abstract: The aim of this article was to present Sectoral Analysis of Landscape Interiors (SALI). This method uses the idea of a landscape interior understood as a fragment of a landscape perceived from the level of a person standing at a given point. The analyses were conducted in two stages: stage I-the quantitative stage, and stage II-the qualitative stage. The first part of the research was the analysis of the percentage share of particular elements of landscape interiors in the images perpetuated in photographs, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Moreover, studies conducted in European cities have identified several problems regarding residents' access to residential green areas [18], which constitute an urgent issue related to environmental justice in densely populated areas [33,34]. In the case of Poland, the studies carried out so far have primarily focused on UGSs on a larger scale [35][36][37], informal greenery [15], urban forests [38], more sustainable spatial planning in the context of environmental protection, and the development of residential areas in urban regions [39]. Few studies have been devoted to residential green areas, although researchers dealing with this topic [40][41][42] have not considered the need to raise urban resilience.…”
Section: Urban Green Spaces (Ugs)mentioning
confidence: 99%
“…Moreover, studies conducted in European cities have identified several problems regarding residents' access to residential green areas [18], which constitute an urgent issue related to environmental justice in densely populated areas [33,34]. In the case of Poland, the studies carried out so far have primarily focused on UGSs on a larger scale [35][36][37], informal greenery [15], urban forests [38], more sustainable spatial planning in the context of environmental protection, and the development of residential areas in urban regions [39]. Few studies have been devoted to residential green areas, although researchers dealing with this topic [40][41][42] have not considered the need to raise urban resilience.…”
Section: Urban Green Spaces (Ugs)mentioning
confidence: 99%
“…In reality however, the perception of visual landscapes likely takes place in motion (as the observer moves between vantage points). Therefore, we accounted for this by applying a directional view sequence approach inspired by Sectoral Analysis of Landscape Interiors [54] (the directional view sequence details are described in the method section).…”
Section: Visibility Metrics For Visual Pollution Assessmentmentioning
confidence: 99%